A Studied Some of the Thermal and Electrical Properties for Particulat Polymer Composites - Hadi, E. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This researchs the preparation of particulate polymer composites from Alkyd resin and Iraqi Burn Kaolin which were added as (20%,30%,40%,50%)and comparing  with the  polymer.  It studied Thermal conductivity and Dielectric strength for both of  the Alkyd resin and  the Composite Material.        The result showed an  increase in Dielectric strength after adding the Iraqi Burn Kaolin , also the Thermal conductivity was  increased by adding the Iraqi Burn Kaolin .